2023
DOI: 10.1021/acsnano.3c01016
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from Nonthermal to Thermal Photoluminescence from Metals Excited by Ultrashort Light Pulses

Abstract: Photoluminescence from metal nanostructures following intense ultrashort illumination is a fundamental aspect of light–matter interactions. Surprisingly, many of its basic characteristics are under ongoing debate. Here, we resolve many of these debates by providing a comprehensive theoretical framework that describes this phenomenon and support it by an experimental confirmation. Specifically, we identify aspects of the emission that are characteristic to either nonthermal or thermal emission, in particular, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…While the assumptions of the phenomenological description of the plasmon-to-photon transduction and some standard approximations in the near-field simulation model may partially account for these differences, they underline the still lacunary knowledge of the mechanism of the remote generation of NPL photons in spite of recent theoretical advances. 25,26 Generalization of Holistic Arithmetic and Logic Units. The design, identification, and location of ALU functions with increasing Boolean complexity implemented within plasmonic cavities is a tedious and time-consuming task.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the assumptions of the phenomenological description of the plasmon-to-photon transduction and some standard approximations in the near-field simulation model may partially account for these differences, they underline the still lacunary knowledge of the mechanism of the remote generation of NPL photons in spite of recent theoretical advances. 25,26 Generalization of Holistic Arithmetic and Logic Units. The design, identification, and location of ALU functions with increasing Boolean complexity implemented within plasmonic cavities is a tedious and time-consuming task.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, in contrast to confocal map simulations, , some minor differences are visible in the relative intensities at the apexes. While the assumptions of the phenomenological description of the plasmon-to-photon transduction and some standard approximations in the near-field simulation model may partially account for these differences, they underline the still lacunary knowledge of the mechanism of the remote generation of NPL photons in spite of recent theoretical advances. , …”
Section: Resultsmentioning
confidence: 99%
“…1 d 12 , 50 . To the best of our knowledge, precise numerical modeling of the PLE lineshape for such non-Fermi distributions has not yet been attempted, although several studies have investigated the spectral character of emission with a non-Fermi term 22 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…An isolated single nanostructure avoids ensemble averaging that can obscure the intrinsic mechanisms of NPL, which has motivated the studies of broadband emission from single nanoparticles, dimers, and few-particle aggregates 13 22 . These studies showed that the hot-electron intraband model, while accounting for the PL emission from rough films, may not provide a good approximation for isolated nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The illumination of metallic nanostructures by ultrashort laser pulses at near-IR wavelengths induces a broadband upconverted emission spanning the visible spectral regime. Under high-intensity femtosecond excitation, this nonlinear signal has been shown to be dominated by a thermal luminescence continuum emitted by out-of-equilibrium surface electrons with transiently elevated temperatures. Indeed, following the absorption of the light pulse, the temperature of the electron gas at the surface of the metal can reach thousands of kelvins for about a picosecond , and radiates before equilibrating with the phonons. This nonlinear photoluminescence (N-PL) has been studied on a wide range of plasmonic geometries and materials. , An important feature is the dramatic signal enhancement observed from hot-spots favored by the presence of localized resonances (e.g., at nanoparticles , ). Such local signal enhancements are observed because the luminescence emanates from hot thermal electrons generated at the surface of the metal. ,, Further, in structures sustaining surface plasmon propagation (e.g., nanowires, cavities), N-PL has been shown to be spatially distributed throughout the modal landscape. , Hence, N-PL has been a key observable to unlock ultrafast light–matter interactions, and this response has found numerous usages.…”
Section: Introductionmentioning
confidence: 99%